Harpagophytum procumbens Root Extract Mediates Anti-Inflammatory Effects in Osteoarthritis Synoviocytes through CB2 Activation - Alessia Mariano; Irene Bigioni; Roberto Mattioli; Antonella Di Sotto; Martina Leopizzi; Stefania Garzoli; Pier Francesco Mariani; Pietro Dalla Vedova; Sergio Ammendola; Anna Scotto d'Abusco (MDPI AG, 2022)
The endocannabinoid system is involved in the nociceptive and anti-inflammatory pathways, and a lowered expression of CB2 receptors has been associated with inflammatory conditions, such as osteoarthritis (OA). This suggests that CB2 modulators could be novel therapeutic tools to treat OA. In the present study, the involvement of Harpagophytum procumbens root extract, a common ingredient of nutraceuticals used to treat joint disorders, in CB2 modulation has been evaluated. Moreover, to clarify the effects of the pure single components, the bioactive constituent, harpagoside, and the main volatile compounds were studied alone or in a reconstituted mixture. Human fibroblast-like synoviocytes, extracted by joints of patients, who underwent a total knee replacement, were treated with an H. procumbens root extract dissolved in DMSO (HPEDMSO). The effectiveness of HPEDMSO to affect CB2 pathways was studied by analyzing the modulation of cAMP, the activation of PKA and ERK MAP kinase, and the modulation of MMP-13 production. HPEDMSO was able to inhibit the cAMP production and MAP kinase activation and to down-regulate the MMP-13 production. Pure compounds were less effective than the whole phytocomplex, thus suggesting the involvement of synergistic interactions. Present findings encourage further mechanistic studies and support the scientific basis of the use of H. procumbens in joint disorders.